Evaluation of Photocatalytic and Protein Adsorption Properties of Anodized Titanium Plate Immersed in Simulated Body Fluid - Sawada, Ryoji; Katou, Yuya; Shibata, Hirofumi; Katayama, Max; Nonami, Toru (International Journal of Biomaterials, 2019)
Titanium-based materials are widely used for implant treatments such as artificial dental roots. Surface treatment has the potential to improve not only the biocompatibility but also the chemical and mechanical durability of the surface without changing the mechanical properties of the metal. A relatively thick titanium oxide film can be formed by the anodic oxidation method. Phosphoric acid or sulfuric acid electrolytic solution has previously been used for anodic oxidation. Such anodized films have excellent film hardness, abrasion resistance, and adhesion. In this study, titanium plate was anodized using an aqueous solution of sulfuric acid in which titanium oxide powder was suspended. A 2800-nm-thick titanium oxide film was formed, which was thicker than that obtained using phosphoric acid electrolyte. The titanium plate was immersed in simulated body fluid for 1 day to evaluate the photocatalytic activity and protein adsorption ability, and a homogeneous crack-free hydroxyapatite layer was formed. This titanium plate showed high methylene blue bleaching capacity. The adsorption ability of the acidic protein of the anodized titanium plate subjected to the above treatment was high. This suggests that this titanium plate has antimicrobial properties and protein adsorption ability. Thus, we report that a titanium plate, anodized with a sulfuric acid aqueous electrolyte solution containing suspended TiO2 powder and immersed in simulated body fluid, might behave as an antibacterial and highly biocompatible implant material.